2009
DOI: 10.1111/j.1742-4658.2009.07095.x
|View full text |Cite
|
Sign up to set email alerts
|

Sin3 is involved in cell size control at Start in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae cells control their cell size at a point in late G1 called Start. Here, we describe a negative role for the Sin3/Rpd3 histone deacetylase complex in the regulation of cell size at Start. Initiation of G1/S‐specific transcription of CLN1, CLN2 and PCL1 in a sin3Δ strain occurs at a reduced cell size compared with a wild‐type strain. In addition, inactivation of the transcriptional regulator SIN3 partially suppressed a cln3Δ mutant, causing sin3Δcln3Δ double mutants to start the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Having verified the interaction of dKDM5/LID with SIN3 and the catalytic component of the complex, the HDAC RPD3, we sought to determine the contribution of dKDM5/LID to SIN3 complex functions. Previous work in yeast, flies, and mammals has shown SIN3 to play an important role in regulating progression through the cell cycle [ 9 , 11 , 17 , 46 ]. In Drosophila, in addition to SIN3, other components of the SIN3 complex such as RPD3 and p55 have also been shown to affect cell growth rates of cultured cells [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Having verified the interaction of dKDM5/LID with SIN3 and the catalytic component of the complex, the HDAC RPD3, we sought to determine the contribution of dKDM5/LID to SIN3 complex functions. Previous work in yeast, flies, and mammals has shown SIN3 to play an important role in regulating progression through the cell cycle [ 9 , 11 , 17 , 46 ]. In Drosophila, in addition to SIN3, other components of the SIN3 complex such as RPD3 and p55 have also been shown to affect cell growth rates of cultured cells [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated a good correlation between SIN3 and HDAC direct target genes. Stephan and Koch (2009) found that Sin3 and HDAC Rpd3 were both recruited to promoters of SBF (Swi4/Swi6)-regulated genes (CLN1, CLN2, and PCL1) in yeast. van Oevelen et al (2008van Oevelen et al ( , 2010 showed by ChIP assay that SIN3 directly impacts acetylation levels downstream of the transcriptional start site of target genes in mouse.…”
Section: Snl1 and Snl2 Regulate Gene Transcription Through Histone Dementioning
confidence: 99%
“…Furthermore, mSin3 has been identified as a critical component in the permanent repression of cell cycle genes during differentiation [26]. Although not essential for yeast viability in normal conditions, ySin3 was shown to be important for accurate timing of Swi4/Swi6-regulated gene transcription during G1 and for activation of S phase in daughter cells [27]. Additionally, S. cerevisiae SIN3 was found to be important for cell cycle progression as null mutants of an asynchronous population accumulated in G2 phase relative to wild type cells [28].…”
Section: Introductionmentioning
confidence: 99%